Incentive and entrenchment effects in European ownership - Bennedsen, Morten; Nielsen, Kasper Meisner (Journal of Banking & Finance, 2010)
In a large sample of European firms we analyze the value discount associated with disproportional ownership structures first documented by Claessens et al. (2002). Consistent with a theoretical model of incentive and entrenchment effects, we find higher value discount in family firms, in firms with low cash flow concentration, and in industries with higher amenity value. Furthermore, the discount is higher in countries with good investor protection and higher for dual class shares than for pyramids. We find no impact on operating performance, likelihood of bankruptcy, dividend policy, or growth. Finally, we discuss policy implications of these findings.